ANALISIS REGRESI LOGISTIK ORDINAL UNTUK MEMODELKAN TINGKAT.KEPARAHAN.PENYAKIT HIV/AIDS.DI RUMAH SAKIT DAERAH IDAMAN BANJARBARU - Thaibatun Nissa; Dewi Sri Susanti (RAGAM: Journal of Statistics & Its Application, 2024)
HIV is a virus that infects the immune system cells, thereby damaging the human immune system. AIDS is a collection of symptoms that arise due to the compromised immune system of the human body as a result of a positive infection by the HIV virus. HIV/AIDS remains a complex and significant global health issue. Despite advancements in treatment and prevention, the severity of HIV/AIDS remains a primary focus in healthcare management efforts. This study aims to determine the factors influencing the severity of HIV/AIDS patients at the Regional Hospital of Idaman Banjarbaru using ordinal logistic regression analysis. Ordinal logistic regression is employed to understand the relationship between the dependent variable (severity of the disease) and independent variables, where the dependent variable is ordinal in scale. The data used for this analysis is secondary data extracted from the inpatient medical records of the Idaman Banjarbaru Regional Hospital, comprising a total of 68 cases of HIV/AIDS. Assumed factors influencing the severity of patients include gender, age, duration of hospitalization, education, employment status, marital status, and place of residence. The analysis results indicate a significant relationship between the severity of HIV/AIDS patients and marital status. The highest likelihood of patients experiencing HIV/AIDS is in the divorced response category with a stage 3 category, where the probability value is 0.943. Individuals in the married and divorced categories are 1.53 times more likely to experience HIV/AIDS with a stage 4 status and complications ranging from 3 to 5. Keywords:   Severity of Disease, HIV/AIDS, Ordinal Logistic Regression, Odds Ratio